2016
DOI: 10.1098/rsta.2016.0184
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobicity of the gecko toe pad: biological optimization versus laboratory maximization

Abstract: While many gecko-inspired hierarchically structured surfaces perform as well as or better than the natural adhesive system, these designs often fail to function across a variety of contexts. For example, the gecko can adhere to rough, wet and dirty surfaces; however, most synthetic mimics cannot maintain function when faced with a similar situation. The solution to this problem lies in a more thorough investigation of the natural system. Here, we review the adhesive system of the gecko toe pad, as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 68 publications
3
20
0
Order By: Relevance
“…However, the observed high-frequency shift (105 ± 16 cm −1 ) indicates that the surface of contacting setal tips (i.e., spatulae) must be covered with unbound lipids exposing polar headgroups, instead of the nonpolar tails. This arrangement of unbound lipids on the setal surface inferred from our SFG results is not contradictory to the previously observed high water contact angles on the toe pad, as recent work by Stark et al ( 15 ) demonstrated that superhydrophobicity is a consequence of the hierarchical structure of the toe pad rather than the presence or absence of lipids. Moreover, this lipid arrangement is similar to the arrangement of lipids in mammalian stratum corneum ( 45 , 46 ).…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…However, the observed high-frequency shift (105 ± 16 cm −1 ) indicates that the surface of contacting setal tips (i.e., spatulae) must be covered with unbound lipids exposing polar headgroups, instead of the nonpolar tails. This arrangement of unbound lipids on the setal surface inferred from our SFG results is not contradictory to the previously observed high water contact angles on the toe pad, as recent work by Stark et al ( 15 ) demonstrated that superhydrophobicity is a consequence of the hierarchical structure of the toe pad rather than the presence or absence of lipids. Moreover, this lipid arrangement is similar to the arrangement of lipids in mammalian stratum corneum ( 45 , 46 ).…”
Section: Discussionsupporting
confidence: 61%
“…First, early studies showed that gecko adhesion to hydroxylated surfaces such as glass and alumina was particularly high, which cannot be explained solely by vdW forces because vdW forces are insensitive to surface chemistry. Lower setal adhesion to a silicon wafer coated with a hydrophobic coating compared to a bare silicon wafer further corroborates these results and suggests that forces other than, or in addition to, vdW interactions may contribute to gecko adhesion ( 4 , 15 ). Second, gecko adhesion enhances with increasing humidity at the setal and whole-animal level, implying that capillary forces also play a role in gecko adhesion in humid environments ( 3 , 4 , 7 ).…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…Given that these structures cause unexpected and not yet theoretically understood surface behaviour, further study and characterization of this class of interfaces are needed. Beyond their overall impact on surface properties and applications in interfacial engineering, vertically aligned structures are also omnipresent in nature (gecko toe pads, plant and leaf surfaces) and biology (tissue architectures) [11][12][13][14][15][16][17][18][19][20]. Therefore, identifying methods to replicate these naturally formed structures provides unique avenues to study natural systems and also to implement bioinspiration when addressing engineering challenges.…”
Section: Introductionmentioning
confidence: 99%